Essential role of p53 phosphorylation by p38 MAPK in apoptosis induction by the HIV-1 envelope - Perfettini, Jean-Luc (The Rockefeller University Press, 2005)
The proapoptotic activity of the transcription factor p53 critically depends on the phosphorylation of serine 46 (p53S46P). Here, we show that syncytia containing p53S46P could be detected in lymph node biopsies from human immunodeficiency virus (HIV)-1 carriers, in the brain of patients with HIV-1–associated dementia and in cocultures of HeLa expressing the HIV-1 envelope glycoprotein complex (Env) with HeLa cells expressing CD4. In this latter model, cell death was the result of a sequential process involving cell fusion, nuclear fusion (karyogamy), phosphorylation of serine 15 (p53S15P), later on serine 46 (p53S46P), and transcription of p53 target genes. Cytoplasmic p38 mitogen-activated protein kinase (MAPK) was found to undergo an activating phosphorylation (p38T180/Y182P [p38 with phosphorylated threonine 180 and tyrosine 182]) before karyogamy and to translocate into karyogamic nuclei. p38T180/Y182P colocalized and coimmunoprecipitated with p53S46P. Recombinant p38 phosphorylated recombinant p53 on serine 46 in vitro. Inhibition of p38 MAPK by pharmacological inhibitors, dominant-negative p38, or small interfering RNA, suppressed p53S46P (but not p53S15P), the expression of p53-inducible genes, the conformational activation of proapoptotic Bax and Bak, the release of cytochrome c from mitochondria, and consequent apoptosis. p38T180/Y182P was also detected in HIV-1–induced syncytia, in vivo, in patients' lymph nodes and brains. Dominant-negative MKK3 or MKK6 inhibited syncytial activation of p38, p53S46P, and apoptosis. Altogether, these findings indicate that p38 MAPK-mediated p53 phosphorylation constitutes a critical step of Env-induced apoptosis.